Social conflicts and historical totality in high middle ages (5th-10th century) - Mário Jorge Bastos da Motta (Universidade Estadual de Maringá, 2015)
The study of the great transitions enjoys, in these days, a considerable degree of low status in the field of History. Maybe it's not hard to see the reasons of such absurd contradiction - at least if we consider that the essence of the subject in question lies in the study of the changes and transformations! Postmodernism, denial of the knowability or even the existence of the real, micro-history, fascination for the immobility, the continuities and the resistance to change, a more or less dense 'description', prevalent, are hegemonic tendencies in the historiographical field that help us to understand the feeling, almost widespread nowadays, that the attempted framing of the transition processes is an extemporaneous task, a surpassed demand! I propose, in this paper, in the context of Iberian's High Middle Ages, the analysis of the transition from Antiquity to the Middle Ages in its fundamental structuring elements.